IMPLEMENTASI SAMBA PADA LOCAL AREA NETWORK MENGGUNAKAN LINUX MANDRAKE 9.1 - Halim, Abdul; Kurniawanto, Hadi (Jurnal Ilmiah Sistem Informasi, 2023)
Linux as a free, open (Open Source), and stable Operating System, has  very high Internet and networking capabilities. This can be proven by the number of companies engaged in Internet services and e-commerce using Linux as the main Operating System on its Server, such as eToys.com, freshmeat.net, Mweb.co.id, Satunet Group, and others. All  Linux software can be freely owned under the GNU General Public License. Based on the license, anyone can have a program in both source code (readable by humans) and binary (machine language), so that the program can be learned, changed, distributed, or further developed by anyone. Another case with Microsoft Windows that cannot be freely owned and is required to pay a license at a very expensive price for those who want to have it. In addition, Microsoft Windows is closed (Close Source), where users or users cannot change, copy and distribute the program. Although the Linux Mandrake 9.1 Operating System began to be much loved and in demand, Microsoft's Operating System is still the top priority for computer users in Indonesia. Almost all Linux Mandrake 9.1 users in Indonesia leave some space on their hard drive for the Windows family Operating System. For those who are accustomed to using the Windows Operating System, of course, they are familiar with the term File Sharing, Print Sharing or Drive Mapping. The program application is run to be able to share Resources (Files, Folders and Printers) with  other Client computers  on a network that uses the SMB protocol. To bridge this, a program was created in the Linux environment called Samba, so that Unix / Linux systems can communicate with other Windows-based computers. Samba programs can bridge the complexity of various Unix/Linux Operating System platforms with Windows machines running on a network. Samba is an application of Unix and Linux known as SMB (Server Message Block) protocol. Many Operating Systems such as Windows use SMB to create a Client Server network. From the explanation above, the author raises this issue to be presented into a discussion, so that we can act as our  own network System Administrator, without the need to pay someone else to install and configure Samba on  a Linux 9.1-based Server Computer Mandrake 9.1.